ELF and teacher education: attitudes and beliefs - Dewey, Martin; Pineda-Hernández, Inmaculada Concepción (English Language Teaching, 2020)
The growing relevance of research in English as a lingua franca (ELF) for ELT has led to a need to rethink the way we approach English in the language classroom and to reassess how we configure knowledge about language in teacher education. This article reports on a joint project conducted at King’s College London (UK) and the University of Málaga (Spain), exploring the value of perceptions towards language and ELF among language teachers. Our goal was to promote reflective attitudes towards linguistic diversity, language change and the potential impact of ELF on developments in ELT. A key objective underpinning our research is to encourage teachers to (re)examine existing beliefs and practices to help envisage alternative, more “ELF informed” perspectives on English and language learning. Our discussion will draw comparisons between both institutions, with a focus on attitudes and responses to ELF research and debate.
Keywords: Inglés - Estudio y enseñanza; English as a lingua franca; Linguistic attitudes; Teacher knowledge; English as a lingua franca pedagogy; Language teacher education